Cognitive decline and mortality in a community-based sample of homeless and precariously housed adults: 9-year prospective study. Issue 2 (March 2020) - Gicas, Kristina M.; Jones, Andrea A.; Thornton, Allen E.; Petersson, Anna; Livingston, Emily; Waclawik, Kristina; Panenka, William J.; Barr, Alasdair M.; Lang, Donna J.; Vila-Rodriguez, Fidel; Leonova, Olga; Procyshyn, Ric M.; et al.
Abstract : Background: Homeless and precariously housed individuals experience a high burden of comorbid illnesses, and excess mortality. Cross-sectional studies report a high rate of cognitive impairment. Long-term trajectories have not been well investigated in this group. Aims: To longitudinally assess risks for premature and/or accelerated cognitive ageing, and the relationship with early mortality in homeless and precariously housed people. Method: This is a 9-year community-based study of 375 homeless and precariously housed individuals from Vancouver, Canada. Annual cognitive testing assessed verbal learning and memory, and inhibitory control. Linear mixed-effects models examined associations between clinical risk factors (traumatic brain injury, psychotic disorders, viral exposure, alcohol dependence) and cognitive change over 9 years. Cox regression models examined the association between cognition and mortality. Results: Traumatic brain injury and alcohol dependence were associated with decline in verbal memory. Inhibitory control declined, independent of risk factors and to a greater extent in those who died during the study. Better inhibitory control was associated with a 6.6% lower risk of mortality at study entry, with a 0.3% greater effect for each year of life. For each one-point increase in the Charlson Comorbidity Index score at study entry, the risk of mortality was 9.9% higher, and was consistent across age. Adjusting for comorbidities, inhibitory control remained a significant predictor of mortality. Conclusions: Findings raise the possibility of a premature onset, and accelerated trajectory, of cognitive ageing in this group of homeless and precariously housed people. Traumatic brain injury, alcohol dependence and cognition could be treatment priorities.